A seeded seroma transforming into tract Metastases: Rare complications of image-guided pleural biopsies - Wui Mei Chew; Ken Junyang Goh; Jessica Thorne; Alguili ElSheikh; Najib M. Rahman (Respiratory Medicine Case Reports)
Seromas are rare complications of ultrasound-guided pleural biopsies, and have not been described to be seeded with tract metastases before. We describe a case where a post-pleural biopsy seroma appeared to be resolving, but developed into a chest wall metastasis over a period of five months. This was an 84-year-old lady undergoing investigation for a malignant pleural effusion, and underwent a left pleural aspiration and ultrasound-guided pleural biopsies in the same sitting. The seroma presented as a painful swelling immediately after pleural biopsy, and was initially conservatively managed due to patient preference. Drainage of the effusion was performed two months after the procedure, and alleviated the patient's breathlessness but did not alter the resolution of the seroma. Serial ultrasound images illustrate the gradual changes in morphology from a hypoechoic collection to an echogenic, organized lesion with lobulated margins. In this case, despite the shrinking size of the original lesion, the patient's persistent pain and atypical ultrasound features of a solid lesion were suspicious for malignant transformation. Chest wall biopsy confirmed metastatic seeding five months after initial intervention. This case highlights the need for heightened surveillance for the development of tract seeding in patients with malignant effusion and seroma after pleural intervention. Delay in chest drainage may have contributed to the poor outcome.